Influence of Spherical and Cylindrical Capsules on Pressure Transients in Hydraulic Pipelines - Samra, Rajbir S. (My University, 1970)
The influence of capsules on pressure transients in hydraulic pipelines has been reported in this dissertation. This experimental investigation was carried out for flow velocities of 1 to 4 ft/sec. for both cylindrical and spherical capsules. Shock waves were generated by a fast closing valve in a 1 in. diameter pipe and pressure transients were measured for a train of cylindrical capsules of diameter 0.875 in. and 0.95 in. The spherical capsules were of diameter 0.75 in. and 0.875 in.
A theoretical analysis for this type of waterhammer problem using a perturbation technique has been obtained. The theoretical solution was found to be in agreement with the experimental observations for cylindrical capsules.
Title: Influence of Spherical and Cylindrical Capsules on Pressure Transients in Hydraulic Pipelines, Author: Rajbir S. Samra, Location: Thode